PELATIHAN CAREER HAPPINESS PLAN UNTUK MENINGKATKAN KEKUATAN KARAKTER (VIRTUE) SEBAGAI MODAL KERJA PADA MAHASISWA - Prasetyo, Anggun Resdasari; Ratnaningsih, Ika Zenita (Faculty of Psychology, Diponegoro University, 2019)
Character strength becomes a major issue in positive psychology research. In the positive psychology, the thing that takes precedence is how to make individuals with all their potential better and develop as optimally as possible. Students who excel are individuals with high achievement motivation, strive to determine specifics goals, use strategic steps, are high-willed, and always work hard to achieve the goals and objectives set. This study aims to determine the effectiveness of Career Happiness Plan training to improve character strength (virtue) as working capital for students. The subjects in this study were 54 students of the Faculty of Psychology, Diponegoro University. Using random assignment technique, subjects were divided into two groups, which consisted of 27 students in the experimental group (8 males; 19 females) and 27 students in the control group (10 males; 17 females). Data were collected through The Values in Action-Inventory of Strenghts (VIA-IS). The results of the t-test on the posttest data between the experimental group and the control group showed a significant difference (t = 2.113; df = 52; p = .039; p <.05). The experimental group had a higher positive character level (M = 487.78; SD = 38.41) than the control group (M = 462.11; SD = 50.07). This explains that the research hypothesis (Ha) is accepted, Career Happiness Plan training can be used to improve character strength (virtue) in students.